Visualizing taste how business changed the look of what you eat - Hisano, Ai (Harvard studies in business history ;, 2019)
Explores transformations in what Americans conceived as a "natural color" of food between the 1870s and 1970s. It analyzes the role of business in creating the modern world of the senses by focusing on the origins and development of the use of visual appeals, particularly color, as a key driver of demand in the food industry in the United States. By examining the development of color controlling technology, government regulation, and consumer expectations, Ai Hisano demonstrates that scientists, farmers, food processors, dye manufacturers, government officials, and intermediate suppliers co-created a "natural" color for food that was, in fact, a hybrid of nature and technology. Color management thus became a central and permanent part of food manufacturing and marketing strategies.